Targeting Renin–Angiotensin System Against Alzheimer’s Disease - Gebre, Abadi Kahsu; Altaye, Birhanetensay Masresha; Atey, Tesfay Mehari; Tuem, Kald Beshir; Berhe, Derbew Fikadu (Frontiers in Pharmacology, 2018)
Renin Angiotensin System (RAS) is a hormonal system that regulates blood pressure and fluid balance through a coordinated action of renal, cardiovascular and central nervous systems. In addition to its hemodynamic regulatory role, RAS involves in many brain activities, including memory acquisition and consolidation. This review summarizes studies on the involvement of the RAS in the pathology of Alzheimer’s disease (AD), and the outcomes of treatment with RAS inhibitors. We summarized the influence of brain RAS in the amyloid plaque (Aβ) formation, which is considered as the pathological hallmark of AD. Angiotensin II (Ang II) is reported to increase brain Aβ level via different mechanisms including increasing amyloid precursor protein (APP) mRNA, β-secretase activity, and presenilin (PS) expression. Ang II was also reported to increase GSK3b mediated tau phosphorylation, and reactive oxygen species (ROS) generation. Moreover, Angiotensin receptor blockers (ARBs) and angiotensin converting enzyme inhibitors (ACEIs) were reported to reduce cognitive decline. Targeting RAS in the brain may benefit patients with AD though it still requires further in depth understanding.